OPTIMALISASI PEMANFAATAN TEKNOLOGI DIGITAL DALAM PEMBUATAN KONTEN VIDEO PEMBELAJARAN BAGI KARYAWAN REGHAS GLOBAL EDUCATION - Nurhayani Lubis; Hardi Hardi; Nofrizal Nofrizal; Sri Maryanti; Inova Fitri Siregar (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This community service activity aimed to optimize the use of digital technology in video content creation for employees of PT Reghas Global Education. Digital transformation in the education sector requires institutions to possess creative and professional video content production capabilities; however, employees’ technical competencies remain limited. The activity was implemented through technical training, hands-on practice mentoring, and the strengthening of digital branding strategies. Evaluation was conducted using questionnaires administered before and after the activity. The results showed a 60 percentage-point increase in participants categorized as understanding/very understanding, shifting from an initial condition dominated by the less understanding category to a dominant level after the training. In addition, the less understanding category decreased to 0% at the end of the activity. These findings indicate that practice-based training methods are effective in improving employees’ competencies and self-confidence. This community service activity is expected to support service quality improvement, institutional image strengthening, and sustainable utilization of digital technology at PT Reghas Global Education.